Innovative Approaches in Business Development Strategies Through Artificial Intelligence Technology - Stevany Edilia; Novia Diah Larasati (Pandawan Sejahtera Indonesia, 2023)
This study explores the key role of artificial intelligence (AI) in changing business development strategies in an era characterized by rapid technological progress. The goal of this research is to find innovative ways to integrate artificial intelligence into corporate operational structures to increase competitiveness and efficiency. Adopting a qualitative research design, this study conducts an in-depth analysis of the literature retrieved from Google Scholar using a systematic approach to presenting data reduction and drawing conclusions. Research shows that integrating AI into business strategy improves existing operations. It emerges as a catalyst for sophisticated data analytics that drive personalized customer experiences and improve decision-making. This study highlights the transformative potential of artificial intelligence to create dynamic business environments where predictive analytics and customer insights inform strategic decisions. A key innovation of this research is its focus on the symbiotic relationship between artificial intelligence and human decision-making. This indicates a paradigm shift in the formulation of business strategy where artificial intelligence becomes not just a tool but a strategic partner that complements human ingenuity. This approach highlights the importance of connecting AI capabilities with human insights to create innovative business strategies that are responsive and adaptable. In conclusion this study provides a comprehensive understanding of the transformative impact of artificial intelligence on business development strategies. It provides valuable insights for organizations looking to use AI for strategic advantage by highlighting the need for a balanced integration of technology and human expertise in an ever-changing business environment.